Susceptibilidad a antimicrobianos en Haemophilus paragallinarum aislados de aves comerciales - Mendoza, Alfredo (2003)
Infectious Coriza (IC) is a disease of the upper respiratory tract of commerdal birds, is caused by Haemophilus paragallinarum, prevented through vaccines and treated by several antimicrobials. With the objective of determining the sensitivity of most used-anti Infectious Coriza antimicrobials, nineteen strains of H. paragallinarum isolated from beeders layer hens and broiler chickens with typical symptoms of IC, from different avian regions of Peru were used. The minimal inhibitory concentrations to trimethoprim, sulfamethoxazole, amoxicillin, gentamicin and enrofloxacin were determined through the microdilution method reconunended by the National Committee for Clinical Laboratory Standards. All strains of H paragallinarum were resistant to sulfamethoxazole; intermediate sensitivity and / or resistant to trimethoprimand and trimethoprim-sulfamethoxazole, gentamicin and amoxicillin, but sensible to enrofloxacin.